PENGARUH STRUKTUR MODAL, PROFITABILITAS, UKURAN PERUSAHAAN, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2011-2014) - Reza Noor Najma, 11.05.52.0159; Lisiantara, Greg Anggana (Students' Journal of Accounting and Banking, 2016)
This study examined the analysis of the influence of the structure of capital structure, profitability ,company size, age companies and debt policy to the value of the company. The research was done in the Indonesia Stock Exchange (IDX) using manufacturing company going public. The purpose of this study was to determine the effect of capital structure, profitability ,company size,and dividen payout ratio to the value of the company. in companies listed on the Stock Exchange during the study periode 2011-2014. The data obtained from the financial statements of publicly traded companies at IDX. The number of samples is 217 manufacturing company. Data analysis method used is multiplelinear regression analysis was used to test the effect of two or more variables between the independent variables, namely the capital structure, profitability, company size,and dividen payout ratio to the value of the company of the companies listed in Indonesia Stock Exchange (IDX) as the dependent variable. The results showed individual profitability and firm size are significant positive effect on the value of the company, the dividen payout ratio is positive not significant of the value of the company, capital structure isn’t significant negative effect on the value of the company.Keywords: Capital Structure, Profitability, Company Size, Deviden Payout To The Value Of The Company